SOCIALIZATION OF REPRODUCTIVE HEALTH IN ADOLESCENTS SCHOOL FOR STUDENTS, INDONESIAN QUR'AN SCHOOL BANDAR LAMPUNG - Wahyuni, Sri; Nur Izzati, Syahdila; Wahyudi, Anang; Abadi, Adelia Nurul; Puspita, Elvia; Artina, Selvi; Sari, Yunita; Anggraini, Devita; Saputri, Desty Alifia; Ab, Fitriana; Aryawati, Wayan (HEARTY, 2024)
Background: Adolescence is a transition period from childhood to adulthood which is marked by the speed of growth and development both physically, mentally, emotionally and socially. The process of adolescent growth and development must receive special attention so that it can be controlled during this phase. Problems that occur in teenagers such as early marriage, premarital sex, pregnancy outside of marriage, abortion, HIV, and AIDS are caused by a lack of information about reproductive health. The aim of the research: is to determine the description of adolescent knowledge about reproductive health at the Indonesian Qur'an School in Bandar Lampung. Research methodology: descriptive research with a research design using a cross-sectional approach. The instrument used is a questionnaire with an ordinal scale. The total sample was 21 teenagers taken using saturated sampling. Research results: show that adolescent knowledge about reproductive health is in the good category at 81% (17 people), and poor knowledge is 19% (4 people). Most teenagers' knowledge about reproductive health is sufficient. Conclusions and Recommendations: It is hoped that the results of this research will be a consideration for carrying out reproductive health education for school-age adolescents to be aware of the high incidence of sexuality and anxiety in parents. Apart from that, the results of this research can also be a basis for future researchers to develop management interventions to overcome adolescents' lack of knowledge in reproductive health.